2013
DOI: 10.1371/journal.pone.0068797
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Staphylococcus aureus Phage ISP after Freeze-Drying (Lyophilization)

Abstract: Staphylococcus aureus phage ISP was lyophilized, using an Amsco-Finn Aqua GT4 freeze dryer, in the presence of six different stabilizers at different concentrations. Stability of the lyophilized phage at 4°C was monitored up to 37 months and compared to stability in Luria Bertani broth and physiological saline at 4°C. Sucrose and trehalose were shown to be the best stabilizing additives, causing a decrease of only 1 log immediately after the lyophilization procedure and showing high stability during a 27 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 29 publications
3
105
3
Order By: Relevance
“…From the perspective of feasibility for therapeutic application, we determined that the stabilities of phages phiIPLA-RODI and phiIPLA-C1C at various pHs and temperatures were very similar to those described for related phages, such as MSA6 (49) and Romulus and Remus (28), and therefore that these phages are suitable for design of different pharmaceutical formulations by lyophilization (50), spray drying (51), and aerosolization (52). Bioinformatic analysis of the phiIPLA-RODI and phiIPLA-C1C genomes showed the typical characteristics of the "Twort-like viruses" (Spounavirinae subfamily): strictly virulent, with large genomes (127 to 140 kb) containing LTRs, genes grouped into modules that are not clearly separated, a few genes encoding tRNAs, and the presence of group I introns (42).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…From the perspective of feasibility for therapeutic application, we determined that the stabilities of phages phiIPLA-RODI and phiIPLA-C1C at various pHs and temperatures were very similar to those described for related phages, such as MSA6 (49) and Romulus and Remus (28), and therefore that these phages are suitable for design of different pharmaceutical formulations by lyophilization (50), spray drying (51), and aerosolization (52). Bioinformatic analysis of the phiIPLA-RODI and phiIPLA-C1C genomes showed the typical characteristics of the "Twort-like viruses" (Spounavirinae subfamily): strictly virulent, with large genomes (127 to 140 kb) containing LTRs, genes grouped into modules that are not clearly separated, a few genes encoding tRNAs, and the presence of group I introns (42).…”
Section: Discussionmentioning
confidence: 77%
“…The susceptibilities of S. aureus IPLA16, S. epidermidis LO5081, and their respective BIMs to several NaCl concentrations were evaluated by determining the 50% lethal dose (LD 50 ) values, defined as the concentration of NaCl that inhibited the growth of the strain by 50% compared with the control culture of the same strain growing in standard TSB (0.5% NaCl). Overnight cultures were diluted to an OD 600 of 0.05 in TSB containing different NaCl concentrations (0.5 to 20%).…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after immobilization, phages showed a titer loss of 1.8 log/mL and 5.0 log/mL for 1% and 5% PEG6000 concentrations respectively. Titer loss was also observed after storage for 37 months (loss of 3 log/mL for 1% PEG6000 and 1.7 log/mL of the titer for 5% PEG6000) (10). These observations were also confirmed by Puapermpoonsiri et al (2010), who showed that PEG6000 as a cryoprotectant at concentrations of 1% and 5% was detrimental for phage specific to Staphylococcus aureus but also for phage specific to Pseudomonas aeruginosa (16).…”
Section: Discussionmentioning
confidence: 65%
“…The immediate decrease in titer after lyophilization varied between 0.6 and 1.4 log/mL, and the best results were obtained in the case of 0.8 M and 1.0 M sucrose, with loss of only 0.4-0.5 log/mL. During the 27-month storage period, the activity of ISP remained stable, with variations within one log/mL in all preparations, except for 0.3 M trehalose (10). Also, in studies presented by Puapermpoonsiri et al (2010), higher loss of activity was observed for phages lyophilized with high concentrations of sucrose (0.5 M) than with lower concentrations (0.1 M) (16).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation